Carotid artery intima–media thickness in non-diabetic hypertensive patients and their correlation with microalbuminuria: A cross-sectional study - Bhusal, Khema Raj; Khanal, Umesh; Pathak, Surya; Khanal, Pratik; Bhattarai, Madhur; Gyanwali, Pradip; Simkhada, Rabindra; Oli, Krishna Kumar (Nepalese Heart Journal, 2025)
Background: Carotid artery intima-media thickness (IMT) is an early indicator of atherosclerosis and a predictor of cardiovascular disease. Hypertension, prevalent globally, is linked to metabolic risk factors and damages carotid artery characteristics. Microalbuminuria signals endothelial dysfunction, increasing the risk of stroke and cardiovascular events.Objective: The objective of the study was to determine the prevalence of carotid artery changes in non-diabetic hypertensive patients and its correlation with microalbuminuria.Methods: A quantitative cross-sectional study was done in 107 participants diagnosed as non-diabetic hypertensive patients visiting Manmohan Memorial medical college and Teaching hospital and Manmohan Cardio-thoracic Vascular and transplant Centre from January 2020 to August 2020. Carotid IMT was measured using B-mode ultrasound, and microalbuminuria was assessed by spot urine albumin-to-creatinine ratio. Data were analyzed using chi-square test and Pearson correlation.Results: The prevalence of abnormal carotid artery IMT is 16.8% and microalbuminuria is 26.2%. No significant association was found between IMT status and micro-albuminuria status (p=0.315). Additionally, there was no significant correlation between IMT and urine albumin level (r=-0.167, p=0.086).Conclusions: The level of microalbuminuria was similar in non-diabetic hypertensive patients, whether or not they had carotid artery changes. However, there was no significant difference between the two groups.